The radiative impact of clouds on the response of the midlatitude circulation to global warming - Albern, Nicole Brigitte Silvia (Karlsruher Institut für Technologie (KIT), 2021)
Clouds and the midlatitude circulation are strongly coupled via radiation. Previous work showed that about half of the annual-mean zonal-mean jet stream and storm track responses to global warming can be attributed to cloud-radiative changes. In this thesis, we investigate the impact of cloud-radiative changes on the global warming response of the midlatitude jet streams and storm tracks across seasons and regions with special focus on the North Atlantic, North Pacific and Southern Hemisphere. To this end, we perform global simulations with the atmospheric component of the ICOsahedral Nonhydrostatic (ICON) model in a present-day setup. We prescribe sea-surface temperatures (SST) to isolate the impact of changes in atmospheric cloud-radiative heating on the midlatitude circulation, and mimic global warming by a uniform 4K or spatially-varying SST increase. We use the cloud-locking method to decompose the midlatitude circulation response into contributions from changes in cloud-radiative properties and from changes in SST. In the first part of the thesis, we investigate the impact of global cloud-radiative changes on the response of the midlatitude jet streams and storm tracks to global warming. In the annual mean, cloud-radiative changes contribute one to two thirds to the poleward jet shift in all three ocean basins and support the jet strengthening in the North Atlantic and Southern Hemisphere. Cloud-radiative changes also impact the storm track, but the impact is more diverse across the three ocean basins. The cloud-radiative impact on the North Atlantic and North Pacific jet streams varies little from season to season in absolute terms, whereas its relative importance changes over the course of the year. In the Southern Hemisphere, cloud-radiative changes strengthen the jet stream in all seasons, whereas their impact on the jet shift is limited to austral summer and fall. The cloud-radiative impact is largely zonally symmetric and independent of whether global warming is mimicked by a uniform 4K or spatially-varying SST increase. In the second part of the thesis, we investigate the relative importance of tropical, midlatitude, and polar cloud-radiative changes for the annual-mean, wintertime, and summertime midlatitude circulation response across regions. Tropical cloud changes dominate the global cloud impact on the 850 hPa zonal wind, jet strength, and storm track responses across most seasons and regions. For the jet shift, a more diverse picture is found. In the annual mean and DJF, tropical and midlatitude cloud changes contribute substantially to the poleward jet shift in all regions. The poleward jet shift is further supported by polar cloud changes across the Northern Hemisphere but not in the Southern Hemisphere. In JJA, the impact of regional cloud changes on the jet position is small, consistent with an overall small jet shift during this season. The jet shift can be largely understood via the anomalous atmospheric cloud-radiative heating in the tropical and midlatitude upper troposphere. The circulation changes are broadly consistent with the influence of cloud-radiative changes on upper-tropospheric baroclinicity and thus the mean potential energy available for conversion into eddy kinetic energy. In the third part of the thesis, we focus on the North Atlantic jet stream response during boreal winter. The eastward extension of the North Atlantic jet stream towards Europe is robust across coupled climate models and atmosphere-only climate models that use prescribed SST. Global cloud-radiative changes contribute robustly to the eastward extension of the jet stream in the three atmosphere-only climate models ICON, MPI-ESM and IPSL-CM5A, but the magnitude of the contribution depends on the model. At the same time, the cloud-radiative changes contribute to model uncertainties in the jet stream response over the North Atlantic. Tropical cloud-radiative changes dominate the impact of global cloud-radiative changes on the eastward extension of the jet stream in ICON. Indian Ocean, western tropical Pacific and eastern tropical Pacific cloud-radiative changes all contribute about equally to the eastward jet extension while tropical Atlantic cloud-radiative changes have a minor impact. The jet response over the North Atlantic due to cloud changes over the tropical Pacific and tropical Atlantic are related to changes in the stationary eddy stream function and the development of Rossby wave trains. No Rossby wave evolves in response to cloud changes across the whole tropics and the Indian Ocean, which indicates that responses in transient eddies might be more important for these regional cloud changes. Our results help to better understand the impacts of cloud-radiative changes. They emphasize the importance of cloud-radiative changes for the regional response of the midlatitude circulation to global warming, and highlight the contribution of tropical cloud-radiative changes for this response. Further, the results indicate that clouds can contribute to uncertainty in model projections of future circulations, in particular due to differences in upper-tropospheric cloud changes.